FORMATION OF PHYSICAL SKILLS THAT INFLUENCE THE MOVEMENT SYSTEM IN THE GROWTH AND DEVELOPMENT OF THE CHILDREN'S ORGANISM. - Mamatova Matluba Abdukhalilovna; Ashurmatov Davlatbek Davronovich (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
The formation of physical competence in school-age children consists in paying attention to the ontogenesis of the bone system, while establishing proper nutrition, and setting up timed physical norms for the daily routine.